2014
DOI: 10.2478/eurodl-2014-0023
|View full text |Cite
|
Sign up to set email alerts
|

Accreditation of Moocs

Abstract: Higher education institutions face conflicting challenges; they must equip students with up-to-date knowledge in fields in which knowledge is constantly being renewed, while they also need to guide students to examine reality through broad-based observation and consider different scientific disciplines. They operate within different constrictions such as: learning program boundaries, budgetary constrictions, and lack of accessibility to experts in different areas, and the range of courses offered to students i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
2
11
0
1
Order By: Relevance
“…This finding can be explained by the fact that platforms and features of MOOCs advance quickly, allowing several new types of content to be integrated into MOOCs (Cisel & Bruillard, 2013). Our results also determined that science, technology, and mathematics, as well as social science, education, and humanities were the content categories covered most, which corresponds with findings from Pundak, Sabag, and Trotskovsky (2014). Second, content was mainly defined in terms of MOOCs' objectives, prerequisites required for participation in the MOOC, teaching scenarios, and, rarely, through strategies used to convey content.…”
Section: Discussionsupporting
confidence: 81%
“…This finding can be explained by the fact that platforms and features of MOOCs advance quickly, allowing several new types of content to be integrated into MOOCs (Cisel & Bruillard, 2013). Our results also determined that science, technology, and mathematics, as well as social science, education, and humanities were the content categories covered most, which corresponds with findings from Pundak, Sabag, and Trotskovsky (2014). Second, content was mainly defined in terms of MOOCs' objectives, prerequisites required for participation in the MOOC, teaching scenarios, and, rarely, through strategies used to convey content.…”
Section: Discussionsupporting
confidence: 81%
“…Though MOOCs partly eliminated the deficiencies of OER, it has also unique criticisms such as lack of interaction between instructors and students (Hill, 2013;Billington & Fronmueller, 2013), unavailable course credits (Shen & Kuo, 2015), reliability of learning (Pundak et al, 2014), questionable course quality (Chen, 2014), sustainability (Universities UK, 2013), ineffective assessments (Shen & Kuo, 2015), and a high dropout rate (Daniel, 2012;Fischer, 2014;Sandeen, 2013a;Yousef, Chatti, Schroeder, & Wosnitza, 2014). These deficiencies will likely continue until MOOCs mature or transform to a new form.…”
mentioning
confidence: 99%
“…Similarly, Sandeen (2013a) argued that online identity management must be resolved before awarding credit for MOOCs. That is, it should be ensured that the person who enrolls in the course is the same person who takes the exam (Pundak et al, 2014;Sandeen, 2013a). In a survey conducted with professors who taught MOOCs, only a quarter of them stated that those who passed the MOOC deserved credit (Kolowich, 2013b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, other initiatives remarks that online learners, compared with blended, report the perception of more workload and less clear courses' instructions (Lim et al, 2007). This suggests important consideration regarding psychological state of learners that has to be taken into account in designing clear online instruction and in handling learners' questions and requests (Pundak et al, 2014); specifically ensuring, as reported by Swan et al (2001): i) frequent and quality interaction with instructors; ii) dynamic Table 1 GDEE Competencies, adapted from (CSCT, 2008;Segal as et al, 2010;Svanstr€ om et al, 2008;Wiek et al, 2011).…”
Section: National Implementation Strategiesmentioning
confidence: 99%